Efeito da sacarose e sorbitol na conservação in vitro de Passiflora giberti N. E. Brown - Faria, Gláucia Amorim [UNESP]; Costa, Maria Angélica Pereira de Carvalho; Junghans, Tatiana Góes; Ledo, Carlos Alberto Da Silva; Souza, Antônio Da Silva (FapUNIFESP (SciELO), 2006)
This work objectified the study of sucrose and sorbitol effect in the in vitro conservation for Passiflora giberti N. E. Brown, access. Therefore, an experiment was conducted in a completely randomized design to compare control treatment (standard MS) to MS medium supplemented with three sucrose concentrations (0, 15 and 30 g L -1) combined with three sorbitol concentrations (10, 20 and 40 g L -1), in a total of 10 treatments with 20 replicas. The experiment evaluation was carried out at 30, 60, 90 and 120 days of incubation, whereas the height of shoots (cm), number of roots, number and color of leaves were observed. The results showed the possibility to maintain passion-fruit microplants for a four months period under slow growth in MS medium supplemented with 10 or 20 g L -1 of sorbitol, without sucrose, and kept under 16 hours photoperiod (22 μ E m -2 s -1) and temperature of 27 ± 1°C. Sucrose sustained the longest development of the microplants. Root formation was affected by the sorbitol in the concentration of 40 g L -1 and by the absence of sucrose in the culture medium.
Sucrose and sorbitol effect in the in vitro conservation of Passiflora giberti N. E. Brown
Keywords: Carbon sources; Passifloraceae; Reduced growth; Passiflora edulis; Passiflora giberti